STRUKTUR SEMIOTIK CERITA KEN AROK KARYA TJAHYANINGTYAS DAN ZHAENAL FANANI - Martutik Martutik (EDU-KATA, 2021)
The tittle of this reserch is “Struktur Semiotik cerita Ken Arok karya Tjahyaningtyas and Zhaenal Fanani, Todorov Teori.” Novel Ken Arok Ken Dedes made of Tjahyaningtyas, and Ken Arok Sumelang Gandring made of Zhaenal Fanani. “Have the goal, this goal is to analiyse semiotic struktur. This reserch is the objective semiotic struktur methode. The source of the data is ken arok ken dedes made of Tjahyaningtyas and ken arok sumelang gandring made of zhaenal Fanani. The focuse of the resech in the problem related to the structure ang semantic. In this written will be analysed by 3 aspec, thera are : sematic aspec, sintacsis aspec, and verbal aspec. The result of the research are : First, sintacsis aspep analyse, consist of coherence of part of thd data, logic coherence, and cronologic coherence, second semantic aspec analyse relationship beetween semantic (in presense) and relationship paradigmatic (in absense), Therd verbal aspect, analyse someting related to the 4 categories, They are : Modus and time categories, knowledge categories, teller categories and, kinds of the language categories.